SWITCHING COST SEBAGAI MEDIASI PADA PENGARUH KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA PENGGUNA IPHONE DI KOTA MALANG) - Rohmi, Aanisa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study tries to identify switching cost as a mediator of the influence of customer satisfaction on customer loyalty. This explanatory research explains the casual relationship between its variables by testing the hypotheses.The sample of this study is 110 respondents that are selected through non- probability sampling technique. The analysis is carried out using Partial Least Square (PLS) with 3.0 SmartPLS, and Sobel test is used to examine the relations of the mediating variables in the hypothesis.The analysis shows that customer satisfaction has a significant relation with switching cost and customer loyalty. Further, switching cost has a significant effect on customer loyalty. Thus, through indirect influence, customer satisfaction and customer loyalty through switching cost generate positive and significant relation.Â Keyword: Customer Satisfaction, Switching Cost, Customer Loyalty